THE ROLE OF INTEREST RATES ON THE EFFECT OF NON-PERFORMING LOANS AND CAPITAL ADEQUACY RATIOS ON BANKING PROFITABILITY (CASE STUDY ON CONVENTIONAL COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE 2016-2020) - Maria Safitri; Vicky Oktavia (Bajang Institute, 2022)
The purpose of this study was to determine the effect of Non Performing Loans (NPL), Capital Adequacy Ratio (CAR) on Profitability (ROA) moderated by Interest Rates (RATE). The population of the data taken in this study were 41 conventional commercial banks. Based on the purposive sampling technique, 190 data samples were obtained from 38 conventional commercial banks listed on the IDX from 2016 to 2020. This study used path analysis with the Warp PLS 7.0 application. The results of this study prove that NPL has a negative and significant effect on ROA, CAR has a positive and significant effect on ROA, interest rates are able to moderate the effect of NPL on ROA of conventional commercial banks as evidenced by the coefficient value of -0.272 with p-value <0.001. However, interest rates are not able to moderate the effect of CAR on ROA of conventional commercial banks.